Environmental Management of the Inle Lake in Myanmar - Lwin, Zaw; Sharma, M.P. (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
The Inle Lake, the second-largest lake in Myanmar, is located in Shan State in Myanmar. More than 170,000 people inhabit the lake and its surroundings, and their main business is agriculture with the fl oating gardens. Due to its picturesque siting and diverse fauna, combined with the unique lifestyles and traditions of human inhabitants, the lake is considered as one of the primary tourist destinations in Myanmar. The Inle is not only designated as the 190th World’s Eco-region but also nominated as one of the fresh water biodiversity hotspots. Since the last decade, the lake has been facing serious threats due to natural and man-made pressure leading to the deterioration of its water quality and shrinkage of the open water area. According to the assessment of its water quality in 2012, the trophic state index of the Inle Lake is found to be in the range of eutrophication. The present paper aims to identify the problems based on data collected from the lake authorities and prepare a management plan for its conservation. The estimated cost is 31.18 million US and is expected to improve the lake health signifi cantly, if the conservation plan is implemented by the government in the true sense. DOI: http://dx.doi.org/10.3126/hn.v11i0.7164 Hydro Nepal Vol.11 2011 pp.57-60